A Conversation with Elisabeth Roudinesco. Issue 1 (2nd January 2019) - Choder-Goldman, Jill
Abstract : In Global Perspectives, we bring you interviews with psychoanalysts from around the world in an effort to explore the influence of culture, politics, and socioeconomics on psychoanalytic training, theory development, clinical technique, and psychoanalytic practice in general.